E-249 Analysis of racial and accessibility disparities with mechanical thrombectomy usage for acute ischemic stroke at a single center. (23rd July 2022) - Abraham, B; Cunningham, C; Jaquish, R; Troja, W; Xu, G; Bohnstedt, B
Abstract : Background: Recent studies describe racial and socioeconomic disparities with mechanical thrombectomy (MT) for acute ischemic stroke (AIS). Our study investigated whether such disparities are present at our institution and the surrounding region. Methods: A retrospective cohort study of 541 patients was conducted at a single institution between January 1, 2017 to March 19, 2020. Patients were grouped based on racial status. We compared demographics, clinical presentation, treatment characteristics, and outcomes. We adjusted for potential confounders such as patient's location (e.g., 'drip and ship', emergency department, in-patient), transfer status (e.g., initial presentation or transferred from an outside facility), transportation method (e.g., Lifeline helicopter or by ground transportation), and analyzed whether racial disparities existed. We defined stroke-onset-to-arrival time as the patient's last known normal to when they arrived at our center. We utilized multivariate analysis to predict 'good' neurological outcomes, defined as a modified Rankin Score (mRS) of 0–2. Results: From a total of 541 patients undergoing MT for AIS, the racial status of 464 patients was reported as White and 77 patients as non-White. There was a significant difference in patients presenting by 'drip and ship' (n=22, 28.6% non-White vs. n=278, 59.9% White), emergency department (n=51, 66.2% non-White vs. n=168, 36.2% White), and in the in-patient setting (n=4, 5.2% non-White vs. n=18, 3.9%) (p<0.0001). Additionally, the difference in transfer status, where patients transferred (n=30, 39.0% non-White vs. n=378, 81.5% White) compared to those who presented initially at our center (n=47, 61.0% non-White vs n=86, 18.5% White), was significant (p<0.0001). When controlling for transfer status, the method of transport was significantly different between those that arrived by Lifeline helicopter (n=6, 20% non-White vs. n=194, 51.3% White) and ambulance (n=24, 80% non-White vs. n=182, 48.7% White) (p=0.001). However, the average distance traveled was also significantly different (34.0 mi, SD 33.9 mi non-White vs. 44.6 mi SD 25.6 mi White) (p=0.008) indicating that non-White patients were transferred from closer locations. The remainder of the clinical, treatment and outcome variables analyzed by transfer status were not significantly different between racial groups (all p>0.05). Analyzing by multivariate regression, racial status did not predict the likelihood of a 'good' neurological outcome (p=0.33). Younger age (p<0.001), shorter stroke-onset-to-arrival time to our hospital (p<0.001), and shorter puncture-to-recanalization times (p=0.005) predicted good neurological outcomes. However, diabetes mellitus (OR 0.47 CI 0.28–0.77, p=0.003) favored poorer outcomes. Conclusion: Racial status was not associated with a difference in clinical presentation, treatment characteristics, nor outcomes. In multivariate analysis, stroke-onset-to-arrival time to our center was the greatest predictor of good neurological outcome. Racial status did not show any significant differences in stroke-onset-to-arrival times at our institution. Disclosures: B. Abraham: None. C. Cunningham: None. R. Jaquish: None. W. Troja: None. G. Xu: None. B. Bohnstedt: 6; C; proctor/consultant.